The Excess of JWST Bright Galaxies: A Possible Origin in the Ground State of Dynamical Dark Energy in the Light of DESI 2024 Data - N. Menci; A. A. Sen; M. Castellano (The Astrophysical Journal)
Recent observations by JWST yield a large abundance of luminous galaxies at z ≳ 10 compared to that expected in the ΛCDM scenario based on extrapolations of the star formation efficiency measured at lower redshifts. While several astrophysical processes can be responsible for such observations, here we explore to what extent such an effect can be rooted in the assumed dark energy (DE) sector of the current cosmological model. This is motivated by recent results from different cosmological probes combined with the last data release of the Dark Energy Spectroscopic Instrument, which indicate a tension in the DE sector of the concordance ΛCDM model. We have considered the effect of assuming a DE characterized by a negative Λ as the ground state of a quintessence field on the galaxy luminosity function at high redshifts. We find that such models naturally affect the galaxy UV luminosities in the redshift range 10 ≲ z ≲ 15 needed to match the JWST observations, and with the value of Ω _Λ = [−0.6, −0.3] remarkably consistent with that required by independent cosmological probes. A sharp prediction of such models is the steep decline of the abundance of bright galaxies in the redshift range 15 ≲ z ≲ 16.